Molecular Subtypes Defined by Cuproptosis-Associated Genes, Prognostic Model Development, and Tumor Immune Microenvironment Characterization in Adrenocortical Carcinoma - Huang Q; Huang XY; Xue YT; Wu XH; Wu YP; Ke ZB; Kang Z; Xu YC; Chen DN; Wei Y; Xue XY; Huang ZY; et al. (Dove Medical Press, 2024)
Qi Huang,1- 3,* Xu-Yun Huang,1,2,* Yu-Ting Xue,1,2,* Xiao-Hui Wu,1,2,* Yu-Peng Wu,1,2,* Zhi-Bin Ke,1,2 Zhen Kang,1,2 Yi-Cheng Xu,1,2 Dong-Ning Chen,1,2 Yong Wei,1,2 Xue-Yi Xue,1,2 Zhi-Yang Huang,3 Ning Xu1,2,4 1Department of Urology, Urology Research Institute, the First Affiliated Hospital, Fujian Medical University, Fuzhou, 350005, People's Republic of China; 2Department of Urology, National Regional Medical Center, Binhai Campus of the First Affiliated Hospital, Fujian Medical University, Fuzhou, 350212, People's Republic of China; 3Department of Urology, Quanzhou First Hospital, Fujian Medical University, Quanzhou, 362000, People's Republic of China; 4Fujian Key Laboratory of Precision Medicine for Cancer, the First Affiliated Hospital, Fujian Medical University, Fuzhou, 350005, People's Republic of China*These authors contributed equally to this workCorrespondence: Ning Xu, Department of Urology, Urology Research Institute, the First Affiliated Hospital, Fujian Medical University, 20 Chazhong Road, Fuzhou, 350005, People's Republic of China, Tel +86-059187981687, Email drxun@fjmu.edu.cn Zhi-Yang Huang, Department of Urology, Quanzhou First Hospital, Fujian Medical University, No. 250, East Street, Licheng District, Quanzhou, Fujian, 362000, People's Republic of China, Email hzy8902@126.comIntroduction: This study aims to explore the role of cuproptosis-related genes in ACC, utilizing data from TCGA and GEO repositories, and to develop a predictive model for patient stratification.Methods: A cohort of 123 ACC patients with survival data was analyzed. RNA-seq data of 17 CRGs were examined, and univariate Cox regression identified prognostic CRGs. A cuproptosis-related network was constructed to show interactions between CRGs. Consensus clustering classified ACC into three subtypes, with transcriptional and survival differences assessed by PCA and survival analysis. Gene set variation analysis (GSVA) and ssGSEA evaluated functional and immune infiltration characteristics across subtypes. Differentially expressed genes (DEGs) were identified, and gene clusters were established. A risk score (CRG_score) was generated using LASSO and multivariate Cox regression, validated across datasets. Tumor microenvironment, stem cell index, mutation status, drug sensitivity, and hormone synthesis were examined in relation to the CRG_score. Protein expression of key genes was validated, and functional studies on ASF1B and NDRG4 were performed.Results: Three ACC subtypes were identified with distinct survival outcomes. Subtype B showed the worst prognosis, while subtype C had the best. We identified 214 DEGs linked to cell proliferation and classified patients into three gene clusters, confirming their prognostic value. The CRG_score predicted patient outcomes, with high-risk patients demonstrating worse survival and possible resistance to immunotherapy. Drug sensitivity analysis suggested higher responsiveness to doxorubicin and etoposide in high-risk patients.Conclusion: This study suggests the potential prognostic value of CRGs in ACC. The CRG_score model provides a robust tool for risk stratification, with implications for treatment strategies.Keywords: cuproptosis, overall survival, immune microenvironment, molecular signature